Letter (copy) - Green, Nan
035-0047-004 COPY INTERNATIONAL BRIGADE ASSOCIATION 374 Gray's Inn Road, London, W.C.1. Dear Brothers, We with to draw your attention to the plight of our Spanish Republican friends in France. Nearly 200 have been arrested by the French authorities during the past few days. Already 150 of them have been deported to North Africa where the notorious and dreaded concentration camps are being re-opened again in the Sahara Desert. It is a sad commentary on things that these men and women, many of whom were decorated for bravery in the French Resistance Movement, are being hounded down and thrown in the self same concentration camps wherein they were kept by the betrayers of France during the Second World War. Why have they been treated in this way? Obviously they have committed no crimes or most surely they would be put on trial. It must be emphasised that these Spanish Democrats have been arrested because of their continued activity and opposition to Franco's Fascist regime. We who remember their glorious struggle against German and Italian Fascism cannot remain silent while such a crime is being perpetrated against them. Their only hope is that the wording class of every country will rally to their aid. The protests of our Trade Union movement can save them from the horrors of these African death camps. We appeal to your organisation to help. Please protest to the French Embassy. We would ask you also to help our campaign funds so that we can campaign until they are restored to their homes, their wives and their children. Yours fraternally, ( sgd. ) NAN GREEN Secretary, INTERNATIONAL BRIGADE ASSOCIATION 292/946/35/47(iv)